Immediate impact of Mindfulness-Based Cognitive Therapy (MBCT) among women with breast cancer: a systematic review and meta-analysis - Yun-Chen Chang; Tzuhui Angie Tseng; Gen-Min Lin; Wen-Yu Hu; Chih-Kai Wang; Yuh-Ming Chang (BMC, 2023)
Abstract Background Mindfulness-based cognitive therapy (MBCT) may have positive physiological and psychological benefits for breast cancer survivors. However, few studies involved a combination of the relevant literatures to confirm the effects. Methods Our study included randomized controlled trials (RCTs) and non-RCTs comparing interventions of MBCT and control protocols for alleviation of symptoms among breast cancer survivors. We calculated pooled mean differences (MDs), standardized mean differences (SMDs), and 95% confidence intervals (CIs) by using random effects models to estimate summary effect sizes. Results Thirteen trials with 20-245 participants were considered in our studies; for the meta-analysis, 11 of these studies were eligible for assessment. The pooled meta-analysis results revealed that at the end of the MBCT intervention, participants' anxiety (SMD, − 0.70; 95% CI, − 1.26 to − 0.13; I 2 = 69%), pain (SMD, − 0.64; 95% CI, − 0.92 to − 0.37; I 2 = 0%), and depression (SMD, − 0.65; 95% CI, − 1.14 to − 0.17; I 2 = 75%) levels significantly decreased, and their mindfulness (MD, 8.83; 95% CI, 3.88 to 13.78; I 2 = 68%) levels significantly increased. Conclusion The MBCT may be associated with improved pain, anxiety, depression, and mindfulness. However, the quantitative analysis pointed to an inconclusive result due to moderate to high levels of heterogeneity among indicator of anxiety, depression, and mindfulness. Future work requires more studies to better elucidate the clinical significance of this possible association. The results suggest that MBCT is highly beneficial as an intervention for patients who have received treatment for breast cancer.